Ictiofauna da Zona de Arrebentação da Praia de Jaguaribe, Itamaracá, Pernambuco : composição, abundância e distribuição mensal - SANTANA, Fábio Magno da Silva (2009)
The fish assemblage structure of the Jaguaribe surfzone, located in the Island of Itamaracá, state of Pernambuco, northeastern Brazil, was analyzed. Samples were collected monthly, from March 2006 until February 2007, in the New and First Quarter moon cycles, during night and day periods. The equipment used for collecting the samples was a beach seine net, 20 m long, 1,5 m high and 5 mm mesh size. A total of 6,407 individuals, belonging to 35 families and 92 species, was collected. Anchoviella lepidentostole;Bairdiella ronchus; Lycengraulis grossidens;Polydactylus virginicus; Larimus breviceps; Anchoa tricolor; Chirocentrodon bleekerianus; Pomadasys corvinaeformis; Stellifer stellifer; Stellifer rastrifer; Lile piquitinga; Conodon nobilis; Menticirrhus americanus; Pellona harroweri and Anchoa marinii dominated quantitatively, representing 90.65% of all specimens captured, being the remainder 9.35% distributed among the other 77 species. There was no significant difference in abundances among months and moon phases, however the daily period abundance was higher than the nocturne one. The surf zone of Jaguaribe beach is dominated by a group of six species (A. tricolor, A. lepidentostole, B. ronchus, L. breviceps, L. grossidens and P. virginicus), which are frequent and abundant throughout the year. This surf zone showed a rich ichthyofauna with a high species diversity most of the months, almost half of them presenting some importance to the fishery in the region. Most species which visit this area are represented by juveniles and small-sized individuals, demonstrating that the site is a nursery ground for many species during their life cycle. The proximity to the Jaguaribe River estuary may be responsible for the high number of species recordedin this place, thus indicating the necessity of a study capable of evaluating the connectivity among these habitats. Finally, such high number of species visiting these sites and the prevalence of juveniles permit to stress the importance of the beach environment for their life cycle and the maintenance of their population stocks. Therefore, these environments deserve an adequate attention, such as the creation of environmental education oriented public policy aiming at awakening resident and visiting population about the importance of preserving such natural nursery grounds.